Bio-inspired Mechatronic Design for the Actuation of a Soft Orthosis for Rehabilitation and Assistance of Hands - Hernández-Sánchez, Jacob (2010)
Proyecto de Graduación (Licenciatura en Ingeniería en Mecatrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Mecatrónica, 2010.